In vitro Spermatogenesis – Optimal Culture Conditions for Testicular Cell Survival, Germ Cell Differentiation, and Steroidogenesis in Rats - Reda, Ahmed; Hou, Mi; Landreh, Luise; Kjartansdóttir, Kristín R.; Svechnikov, Konstantin; Soder, Olle; Stukenborg, Jan-Bernd (Frontiers in Endocrinology, 2014)
Although three-dimensional testicular cell cultures have been demonstrated to mimic the organization of the testis in vivo and support spermatogenesis the optimal culture conditions and requirements remain unknown. Therefore, utilizing an established three-dimensional cell culture system that promotes differentiation of premeiotic murine male germ cells as far as elongated spermatids, the present study was designed to test the influence of different culture media on germ cell differentiation, Leydig cell functionality and overall cell survival. Single-cell suspensions prepared from 7-day-old rat testes and containing all the different types of testicular cells were cultured for as long as 31 days, with or without stimulation by gonadotropins. Leydig cell functionality was assessed on the basis of testosterone production and the expression of steroidogenic genes. Gonadotropins promoted overall cell survival regardless of the culture medium employed. Of the various media examined, the most pronounced expression of Star and Tspo, genes related to steroidogenesis, as well as the greatest production of testosterone was attained with DMEM + glutamine. Although direct promotion of germ cell maturation by the cell culture medium could not be observed, morphological evaluation in combination with immunohistochemical staining revealed unfavorable organization of tubules formed de novo in the three-dimensional culture, allowing differentiation to the stage of pachytene spermatocytes. Further differentiation could not be observed, probably due to migration of germ cells out of the cell colonies and the consequent lack of support from Sertoli cells. In conclusion, the observations reported here show that in three-dimensional cultures, containing all types of rat testicular cells, the nature of the medium per se exerts a direct influence on the functionality of the rat Leydig cells, but not on germ cell differentiation, due to the lack of proper organization of the Sertoli cells.